Profession Zakat in Qanun Perspective/District Code (Perda) of Aceh - Suryani Suryani; Muhammad Anwar Fathoni; Ismaulina Ismaulina (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2019)
Poverty has been a greatest problem in Indonesia. It emerges consideration for community, especially government as regulator because its characteristics multi-dimensionally and complexly have influenced every aspect of human civilization, mainly Indonesian people. Poverty level in Indonesia decreases every year, but the hard attempts to cope with it must be central priority for government to reach national development target: creating welfare for all of Indonesian people. Zakat as a religious instrument that has a mission to empower the poor has been running for so long in this country. However, in the beginning of the New Order era zakat started being driven into state legislation. Zakat has potential to help the government tackle the issue of social justice and welfare. This is consistent with the constitutional mandate. However, due to the unfavorable political situation zakat issues were suspended. In 1999 Law No. 38/1999 was issued. It became a milestone for Indonesian that Islamic Sharia zakat officially became positive legal which meant being legalized by the state. This code was later replaced by Law 23/2011. Unlike the previous law, Law No. 23/2011 provided reinforcement against BAZNAS role as a leading sector in the management of national charity (zakat).